The Financial Performance and Macrofinancial Implications of Large State-Owned Enterprises in Sub-Saharan Africa - Wezel, Torsten (IMF Working Papers; Working Paper ;, 2022)
Using a newly-compiled dataset of state-owned enterprises in Sub-Saharan Africa, we present aggregate information about profitability, liquidity and leverage. We find that 40 percent of the close to 300 surveyed SOEs are unprofitable, while larger firms also tend to be illiquid and overleveraged. In cross-sectional regressions we find that SOE debt stock sustainability is impacted by firms' profitability and liquidity, while macroeconomic factors cannot be shown to matter, expect for some governance variables. Based on these findings and citing country examples, we also illustrate that weak SOE performance may have a macrofinancial impact affecting bank soundness through delinquent loan exposures.